GERMINATION OF CUBIU SEEDS STORAGE UNDER DIFFERENT CONDITIONS OF LIGHT - STEFANELLO, Suzana; CHRISTOFFOLI, Patrícia; FRANTZ, Gracieli; ROCHA, Andressa Camilo de Souza; SILVA, Jaqueline Manzatti da; STEFANELLO, Raquel; SCHUELTER, Adilson Ricken (Scientia Agraria, 2008)
Cubiu (Solanum sessiliflorum Dunal) is a native plant from the Amazonian region which has been expanding outside its origin center. The plant has potential for supplying agri-industrial programmes because the fruit yield is highly significant and it accumulates high levels of dietary iron, niacin and citric acid. Today, there is significant information about cooking, nutritional, and medical characteristics of cubiu plants. On the other hand, agronomic factors like the germination of cubiu seeds are poorly understood and particularly the light quality, which has strong influence on the germination of small seeds. The objective of the present study was to investigate the influence of different light conditions on the germination of cubiu seeds ‘Santa Luzia’ after refrigerator storage at 4 °C for 6 months. The following light conditions were investigated: white, red, far-red, and darkness. The light intensity was provided by four 20 W fluorescent lamps which were attached to the door of the seed germinator. The percentage of seed germination, the speed germination index, the length and dry biomass of seedlings were evaluated. The germination of the seeds occurred under all light conditions, however there were higher percentage of seed germination, germination index, and length of seedlings under red and far-red conditions.